2020
DOI: 10.1038/s41439-020-00126-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel PTCH1 mutations in Japanese familial nevoid basal cell carcinoma syndrome

Abstract: Nevoid basal cell carcinoma syndrome (NBCCS), also known as Gorlin syndrome, is inherited in an autosomal dominant manner and is characterized by a combination of developmental abnormalities and a predisposition to tumor formation. Hedgehog receptor Patched 1 (PTCH1) has been identified as the mutated gene in NBCCS. We identified the PTCH1_c.3298_3299insAAG_p.1099_1100insE mutation in the transmembrane region, which comprises a sterol transporter whose abnormal function is reportedly related to pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Palmoplantar pits, which are in the form of nonpalpable, asymptomatic, and point depressions, are the most common features of GS and can be seen in 35-80% of patients [1][2][3][4][5][6][7][8][9][10]12]. Palmoplantar pits are one of the major diagnostic criteria of GS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmoplantar pits, which are in the form of nonpalpable, asymptomatic, and point depressions, are the most common features of GS and can be seen in 35-80% of patients [1][2][3][4][5][6][7][8][9][10]12]. Palmoplantar pits are one of the major diagnostic criteria of GS.…”
Section: Discussionmentioning
confidence: 99%
“…Gorlin syndrome (GS; OMIM #606593), a rare and multi-systemic disorder with a predisposition to the development of cancer such as medulloblastoma and nevoid basal cell carcinoma (BCC), is reported for the first time by Gorlin and Goltz in 1960 [1][2][3][4][5][6][7][8][9][10][11][12]. The genetic etiology was revealed in 1996 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The PTCH1 p.P1315L mutation has also been identified in solitary OOC and reported to be unrelated to the risk of basal cell carcinoma, which is one of the symptoms of NBCCS [ 9 , 26 ]. Several studies have indicated that PTCH1 p.P1315L is a nonpathogenic mutation [ 9 , 27 ]. Moreover, the interpretation of PTCH1 p.P1315L is “Benign” in ClinVar [ 28 ].…”
Section: Discussionmentioning
confidence: 99%